Portfolio management in new product development lessons from the leaders-II - Cooper, Robert G.
Robert G. Cooper, Scott J. Edgett and Elko J. Kleinschmidt examine how leading firms attempt to link their R&D portfolios to the strategies of their businesses.
Effective portfolio management requires that three elements be in place and working in harmony with one another : the strategy of the business, a new product process with gates, and the portfolio review with its various models and tools.
Three goals were revealed by a study of portfolio management practices in industry : maximizing the value of the portfolio, achieving the right balance and mix of projects, and linking the portfolio to the strategy of the business. The first two goals were examined in the September-October 1997 issue of RTM (1). This second article describes several methods for realizing the third goal, including a strategic "buckets" model, a top-down method for setting spending targets, a bottom-up scoring scheme that emphasizes strategic criteria, and the strategic check, which incorporates elements of both. In the ideal portfolio managemenet process, three decision processes must work together : the strategy of the business drives both the portfolio review (and various portfolio models) as well as the gates or decision points in the business's Stage-Gate new product process. The gating process and the portfolio methods feed each other, and all three must be integrated.
Keywords: Portfolio management; Product development